A New Method of Sectional Expression of Wind Turbine Airfoil Function - Zhaohuang Zhang (MDPI AG, 2021)
To expand the airfoil database and realize the reverse digital airfoil design, this paper proposes a new sectional expression function of wind turbine airfoil based on the Joukowski transformation and derives the function equation for the novel airfoil. Compared with the existing airfoil function, the new airfoil function can adjust the parameter values to control the relative thickness, relative thickness position, relative camber, and relative camber position of the airfoil. Taking the common airfoil (NACA63-212) as an example, the existing airfoil is fitted according to the expected direction. The maximum fitting deviation is <semantics>1.22135×10-3</semantics>, better than the four existing methods for airfoil shape fitting, which demonstrates well the practicability and accuracy of this method. It also shows that changing the parameter values can generate a new airfoil to enrich the airfoil database. Therefore, the proposed method broadens the ideas for airfoil design and method research.